STRATEGI MANAJEMEN KURIKULUM DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SD NEGERI PECABEAN 01 - Anang; Beni Habibi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the suboptimal implementation of curriculum management in improving students' learning outcomes at SD Negeri Pecabean 01, as reflected in lesson planning that has not fully accommodated students' learning needs, limited teacher competence in developing instructional materials, less effective academic supervision, and learning evaluation that remains focused on final scores rather than comprehensive competency development. The study aimed to analyze curriculum management strategies in improving students' learning outcomes at SD Negeri Pecabean 01. This research employed a qualitative approach using a theoretical analysis (library research) method by examining books, scientific journal articles, previous research findings, and relevant documents related to curriculum management and the implementation of the Merdeka Curriculum. Data were analyzed through data reduction, data presentation, interpretation, and descriptive conclusion drawing. The findings indicate that effective curriculum management strategies consist of four main components: curriculum planning based on students' needs, student-centered learning implementation, academic supervision focused on improving teacher competence, and continuous curriculum evaluation. These four components are integrated into a comprehensive curriculum management system that enhances the quality of the learning process and students' learning outcomes. Therefore, systematic and sustainable curriculum management strategies are essential in supporting the improvement of educational quality at the elementary school level.